A THEORETICAL EXTENSION OF TECHNOLOGY ORGANIZATION ENVIRONMENT (TOE) IN E-GOVERNMENT: A SYSTEMATIC LITERATURE REVIEW AND THEORY EVALUATION - Suradi, Agustinus (Journal of Computer Science and Technology (JCS-TECH), 2025)
Currently, the universal influence of information technology has been considered as an important tool in enhancing the performance of local governments in a country. There is a consensus that information technology has a significant impact on good government. This effect will be realized when information technology is widely distributed and used in integrated e-government. Therefore, it is important to understand the determining factors when considering the adoption of information technology. In this article, we review The Technology Organization Environment (TOE) Framework theory for the adoption model in e-government, which is widely used in the information systems literature. The TOE framework identifies three contextual aspects: technology context, organization context, and environment context. We conduct an analysis of the TOE framework and studies that combine the TOE framework with other theories. This research examines the TOE framework and also provides recommendations for future research opportunities